Novel Promising Antifungal Target Proteins for Conquering Invasive Fungal Infections - Zhen, Cheng; Lu, Hui; Jiang, Yuanying (Frontiers in Microbiology, 2022)
Invasive fungal infections (IFIs) pose a serious clinical problem, but the antifungal arsenal is limited and has many disadvantages, such as drug resistance and toxicity. Hence, there is an urgent need to develop antifungal compounds that target novel target proteins of pathogenic fungi for treating IFIs. This review provides a comprehensive summary of the biological functions of novel promising target proteins for treating IFIs in pathogenic fungi and their inhibitors. Inhibitors of inositol phosphoramide (IPC) synthases (such as Aureobasidin A, Khafrefungin, Galbonolide A, and Pleofungin A) have potent antifungal activities by inhibiting sphingolipid synthesis. Disrupting glycosylphosphatidylinositol (GPI) biosynthesis by Jawsamycin (an inhibitor of Spt14), M720 (an inhibitor of Mcd4), and APX001A (an inhibitor of Gwt1) is a promising strategy for treating IFIs. Turbinmicin is a natural-compound inhibitor of Sec14 and has extraordinary antifungal efficacy, broad-antifungal spectrum, low toxicity, and is a promising new compound for treating IFIs. CMLD013075 targets fungal heat shock protein 90 (Hsp90) and has remarkable antifungal efficacy. Olorofim, as an inhibitor of dihydrolactate dehydrogenase, is a breakthrough drug treatment for IFIs. These novel target proteins and their inhibitors may overcome the limitations of currently available antifungal drugs and improve patient outcomes in the treatment of IFIs.